Risk of cardiovascular disease among women with endometrial cancer compared to cancer-free women in the Women's Health Initiative. (December 2017) - Felix, Ashley S.; Lehman, Amy; Foraker, Randi E.; Naughton, Michelle J.; Bower, Julie K.; Kuller, Lewis; Sarto, Gloria E.; Stefanick, Marcia L.; Van Horn, Linda; Jackson, Rebecca D.; Paskett, Electra D.
Highlights: Endometrial cancer (EC) incidence is increasing in the United States. Women with EC have a high prevalence of cardiovascular disease (CVD) risk factors. CVD risk did not differ between women with EC and those who did not develop EC. Abstract: Background: The majority of women diagnosed with endometrial cancer (EC) have low cancer-specific mortality; however, a high prevalence of cardiovascular disease (CVD) risk factors places EC patients at high risk of developing CVD. In the Women's Health Initiative (WHI), we assessed the hypothesis that CVD risk was higher among women who developed EC compared with women who did not develop EC. Methods: We compared the incidence of fatal and non-fatal CVD events among 1, 179 women who developed Type I EC, 211 women who developed Type II EC, and 92, 217 women who did not develop EC. We first estimated univariable cause-specific hazard ratios (CHRs) and 95% confidence intervals (CIs) for the association between an EC diagnosis (overall and by EC type) with CVD risk using Cox proportional hazards regression. Potential confounders were examined using a risk factor modeling approach; final multivariable-adjusted models included covariates that changed univariable CHRs for EC diagnosis by ≥ 5%. Results: In multivariable-adjusted models, CVD risk did not significantly differ between women who developed EC compared to women who did not develop EC (CHR = 1.01, 95% CI = 0.87–1.16), particularly for the subgroup of women who developed Type I EC (CHR = 0.98, 95% CI = 0.84–1.14); however, there was a positive but statistically nonsignificant association for Type II EC (CHR = 1.32, 95% CI = 0.88–1.97). Conclusion: Despite our null findings, women with EC should still receive counseling and support to make lifestyle changes aimed at reducing weight as appropriate, given the high prevalence of CVD risk factors at diagnosis.